Особливості оформлення сучасних настільних ігор - Гаманець, А. (My University, 2020)
The feature of planning of modern table games is examined. Table games for today conquer popularity among teenagers eccentricness of approaches, variety of variants of game and unforeseeable result
Keywords: настільні ігри; оформлення настільних ігор; нестандартні елементи